Comparison of effect of intrathecal dexmedetomidine and clonidine as an adjuvant to hyperbaric bupivacaine in patients undergoing surgery for fracture femur and tibia - Chandra, G. Praveen; Krishna, Sampathi Shiva; Singh, Pooja (International Surgery Journal, 2017)
Background: Spinal anaesthesia with bupivacaine is administered routinely for lower abdominal and lower limb surgeries. The ensuing nerve block is sufficient to ensure patient’s wellbeing, while motor block facilitates the surgeon’s work. Post-operative pain relief can be achieved by various methods namely systemic opioid and non-opioid peripheral nerve blocks and local wound infiltration, each with their own merits and demerits. the present study was undertaken to compare the effect of intrathecal dexmedetomidine and clonidine as an adjuvant to hyperbaric bupivacaine in patients undergoing surgery for fracture femur and tibia. Methods: 80 patients between 20-60 years, undergoing elective surgery for closed fracture shaft of femur and tibia with ASA physical status of 1 and 2 were included in the study. All the subjects were randomly allocated to one of the two groups (Group C and Group D) by a computer-generated randomization chart. Group C received 2.5ml of 0.5% hyperbaric bupivacaine with 50mcg clonidine and group D received 2.5ml of 0.5% hyperbaric bupivacaine with 5mcg dexmedetomidine. Results: 30 of the 40 patients in group C were of ASA I and 10 were ASA II, while in group D, 25 were ASA I and 15 were ASA II. A significant difference was found in the onset time for sensory and motor block, receding time for sensory and motor block and the need of the first rescue analgesia between the two groups, showing that Dexmedetomidine was more potent than clonidine. Conclusions: Dexmedetomidine is a potent, highly selective and specific α2-adrenoreceptor agonist that has both sedative and analgesic effects and is also a valuable adjuvant when regional anaesthesia is incorporated.